(untitled) (World Economics and Finance Bulletin, 2023)
The statement of whether capital structure is in fact a major part of companies’ profitability in North American Oilfield Service companies remains to be a controversial topic. It is ironic that gas and oil industry is hugely profitable and always in the eyes of investors. At the same time, knowing the optimal capital structure combination is in need for those companies especially after the effects of the relatively recent pandemic